2013
DOI: 10.28930/jitkt.v5i1.7741
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Distribution of Benthic Foraminifera at Coral Reef Ecosystem in Thousands Island

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The islands in the study area are located about ~60-70 km in the far northwest from the Jakarta Bay which make the environment is still suitable for reef to develop well. The previous research at Kotok Besar island (Natsir, 2010) and at Karang Bongkok island (Toruan et al, 2013) also concluded that the environment condition of both area are considered conducive for coral reef growth.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The islands in the study area are located about ~60-70 km in the far northwest from the Jakarta Bay which make the environment is still suitable for reef to develop well. The previous research at Kotok Besar island (Natsir, 2010) and at Karang Bongkok island (Toruan et al, 2013) also concluded that the environment condition of both area are considered conducive for coral reef growth.…”
Section: Resultsmentioning
confidence: 92%
“…A similar condition also occurs in Onrust island near Jakarta Bay, exhibiting a bad condition of coral reef. The condition is shown by higher percentages of several opportunistic genera compared to that of genera associated with coral reef (Toruan et al, 2013 (Noor, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study indicate damage to coral reefs at all the observation stations, with the damage being most severe at stations 2 and 3. The causes of such damage are usually coral bleaching, environmental pressure, and human activities (Toruan & Soedharma, 2013). Coral bleaching occurs due to the loss of part of a population of the symbiont algae Symbiodinium and the resulting white discoloration.…”
Section: Biodiversity Habitatmentioning
confidence: 99%